La2SrCr2O7: Controlling the tilting distortions of n = 2 Ruddlesden-Popper phases through A-site cation order - Zhang, R; Abbett, B; Read, G; Lang, F; Lancaster, T; Tran, T; Halasyamani, P; Blundell, S; Benedek, N; Hayward, M (American Chemical Society, 2016)
Structural characterization by neutron diffraction, supported by magnetic, SHG, and μ(+)SR data, reveals that the n = 2 Ruddlesden-Popper phase La2SrCr2O7 adopts a highly unusual structural configuration in which the cooperative rotations of the CrO6 octahedra are out of phase in all three Cartesian directions (ΦΦΦz/ΦΦΦz; a(-)a(-)c(-)/a(-)a(-)c(-)) as described in space group A2/a. First-principles DFT calculations indicate that this unusual structural arrangement can be attributed to coupling between the La/Sr A-site distribution and the rotations of the CrO6 units, which combine to relieve the local deformations of the chromium-oxygen octahedra. This coupling suggests new chemical "handles" by which the rotational distortions or A-site cation order of Ruddlesden-Popper phases can be directed to optimize physical behavior. Low-temperature neutron diffraction data and μ(+)SR data indicate La2SrCr2O7 adopts a G-type antiferromagnetically ordered state below TN ∼ 260 K.